Molecular characterization and genomic organization of fowl adenovirus isolates of Malaysia - Mohd Ayob, Juliana (2014)
Fowl adenoviruses (FAdVs) are ubiquitous in all avian species especially in commercial broiler chickens and some of them are associated with diseases such as inclusion body hepatitis (IBH). Previous study on the pathogenicity of Malaysian FAdV isolate that involved in IBH outbreaks was based on serological method, leaving the serotype identification remained unknown. Thus, the aim of this study was to determine and characterize the FAdV of Malaysian isolates and establish the genomic organization of FAdV of UPM04217 isolate. Five FAdV Malaysian isolates were propagated in specific pathogen free (SPF) embryonated chicken eggs and characterized by the hexon based polymerase chain reaction (PCR) method coupled with restriction enzyme analysis (REA), and followed by direct sequencing. Approximately 1.2 kb and 1.3 kb were generated using H1/H2 and H3/H4 primer pairs, respectively. All isolates generated same restriction enzyme patterns that resembled the digestion patterns of the FAdV-8b, strain 764 when H1/H2 and H3/H4 PCR products were digested by HaeII and HpaII, respectively. Sequence and phylogenetic analysis based on the loop 1 (L1) region of the hexon gene revealed that all Malaysian FAdV isolates that involved in IBH outbreaks were 100% identical and showed highest similarity of 98.1% to FAdV-8b, strain 764. Evolutionary relationship of Malaysian FAdV isolates to FAdV species E was demonstrated by high bootstrap values of 99% in nucleotide sequence by using the distance, maximum parsimony and maximum likelihood methods. The nucleotide sequence of the whole genome of FAdV-8b UPM04217 isolate was determined using next generation sequencing (NGS) platform and the Sanger sequencing method. The complete genome was found to be 44 059 bp long with 57.9% G+C content and shared 97.5% genome identity with reference FAdV-E genome (HGisolate). Interestingly, the genome analysis using ORF Finder, Glimmer3 and FGENESV predicted a total of 40 open reading frames (ORFs) compared to FAdV-E HG isolate that possessed 46 ORFs. Gene nnotation and comparison analysis using BLASTP, EMBOSS Needle and mVISTA-LAGAN programs showed no additional unique gene and the absence of 3 ORFs were also detected (ORF11A, unique ORF and ORF32). In contrast to FAdV-E HG isolate, ORF22, ORF25 and ORF33 in FAdV UPM04217 isolate were encoded by a single ORF rather than two small ORF. However, the genome organization was similar to other FAdV members. Correct identification of the serotypes involved in IBH outbreaks and knowledge of the complete FAdV genome sequence of UPM04217 will provide valuable information on the epidemiological study, molecular evolution, vaccination strategies and for future recombinant vector development purposes.